2004
DOI: 10.1111/j.1364-3703.2004.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Δ12 fatty acid desaturase during the induced accumulation of the antifungal diene in avocado fruits

Abstract: SUMMARY The preformed (Z,Z)-1-acetoxy-2-hydroxy-4-oxo-heneicosa-12,15-diene (AFD) is the most active antifungal compound in avocado; it affects the quiescence of Colletotrichum gloeosporioides in unripe fruit. One of the genes encoding Delta(12) fatty acid desaturase (avfad12) was hypothesized to take part in the biosynthesis of AFD, and its expression pattern and enzymatic activity were determined in relation to the content of AFD. Using avfad12-3 as a probe, high levels of expression were detected in young f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 50 publications
4
20
0
2
Order By: Relevance
“…On the other hand, the observed increase of linoleic acid and the decrease of linolenic acid detected in chloroplast lipids such as MGDG, DGDG, SQ, and PG are consistent with the detected induction of the extraplastidial oleate desaturase FAD2 and the repression of the plastidial desaturases FAD5, FAD6, and FAD8 in infected leaves. The involvement of the FAD2 gene in the response to biotic stresses has been described in parsley (Petroselinum crispum) cell cultures supplemented with a fungal elicitor (Kirsch et al, 1997) and in fungus-infected avocado (Persea americana) fruits (Wang et al, 2004). In these cases, it has been suggested that the accumulation of polyunsaturated fatty acids could compensate for losses caused by the elimination of lipid hydroperoxides from membrane injury during the oxidative burst and/or by the conversion of polyunsaturated fatty acids to signal molecules such as jasmonates (Kirsch et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the observed increase of linoleic acid and the decrease of linolenic acid detected in chloroplast lipids such as MGDG, DGDG, SQ, and PG are consistent with the detected induction of the extraplastidial oleate desaturase FAD2 and the repression of the plastidial desaturases FAD5, FAD6, and FAD8 in infected leaves. The involvement of the FAD2 gene in the response to biotic stresses has been described in parsley (Petroselinum crispum) cell cultures supplemented with a fungal elicitor (Kirsch et al, 1997) and in fungus-infected avocado (Persea americana) fruits (Wang et al, 2004). In these cases, it has been suggested that the accumulation of polyunsaturated fatty acids could compensate for losses caused by the elimination of lipid hydroperoxides from membrane injury during the oxidative burst and/or by the conversion of polyunsaturated fatty acids to signal molecules such as jasmonates (Kirsch et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Table I. Effect of TRV infection on the content and fatty acid composition of lipid classes in Arabidopsis leaves at 8 dpi low-salt and low-temperature tolerance in Arabidopsis, the involvement of the FAD2 gene in response to biotic stress has been widely documented (Miquel et al, 1993;Kirsch et al, 1997;Wang et al, 2004;Zhang et al, 2012). In this scenario, accumulation of polyunsaturated fatty acids could compensate for losses caused by the elimination of lipid hydroperoxides during the oxidative burst (Kirsch et al, 1997).…”
Section: Trv Infection Interferes With Fatty Acid Biosynthesismentioning
confidence: 99%
“…The pH is also changed, or induced to change, by the pathogens around the infection site (Beno-Moualem and Prusky 2000; Wang et al 2004). Thus, an increase in the natural pH during fruit ripening or as a result of fungal activity can suppress oxidative responses of either the pathogen or the host, and so facilitate activation of the quiescent infection.…”
Section: Factors Facilitating Pathogenicitymentioning
confidence: 99%
“…13) Plant fatty acid desaturases are regulated by various environmental factors. 1) Much research suggests that temperature can regulate fatty acid desaturases at the transcriptional and post-transcriptional levels, as described for FAD2 in several plants, 3,5,33) for FAD6 in olive fruit, 34) for FAD3 in wheat roots, 2) and for FAD8 in Arabidopsis leaves, 35) but no effect of temperature on the expression of the Á6-desaturase gene has been demonstrated in higher plants. In the present study, when plants were incubated at low temperature, an increase in MsD6DES expression levels was observed (Fig.…”
Section: Discussionmentioning
confidence: 99%